Effect of sesame protein and lotus starch based bioactive coatings with the incorporation of Garcinia indica extract on the shelf-life extension of sapodilla - Sharma, Loveleen; Saini, Charanjiv Singh; Sharma, Vinita (Journal of Postharvest Technology, 2021)
Sapodilla (Manilkara zapota L.), a climacteric fruit is having high rate of ethylene production which leads to early senescence followed by spoilage. There is need to increase the shelf life of sapodilla after harvesting. Different coating solutions were prepared from sesame protein isolate (SP) and lotus seed starch (LS) with the addition of Garcinia indica extract (GE). Two coats were applied on the fruit with manual drying after an interval of 20 min. Fruits were stored at 70-75 % RH and 20 ±1 ºC temperature in plastic mesh trays in an environment chamber to store all coated and non-coated fruits. Garcinia indica (GE) extract with the combination of sesame protein and lotus starch could maintain the overall quality of sapodilla fruit and extends the shelf life up to 12 days. GE in sesame protein and lotus starch-based coatings helps to retain the nutritional parameters by delaying respiration rate of fruit samples during storage.